Simulation integration: using multidatabase systems concepts. (November 2014) - Jalali, Leila; Mehrotra, Sharad; Venkatasubramanian, Nalini
This paper considers the challenge of designing a framework that supports the integration of multiple existing simulation models into an integrated simulation environment (multisimulation). We aim to facilitate the process of fusing together the independently created simulators into an integrated simulation environment wherein we can model and execute complex scenarios involving multiple simulators. In this paper, we focus on solutions for the synchronization problem in multisimulation to orchestrate consistent information flow through multiple simulators. In particular, we provide: (1) a transaction-based approach to modeling the synchronization problem in multisimulations by mapping it to a problem similar to multidatabase concurrency; we express multisimulation synchronization as a scheduling problem where the goal is to generate "correct schedules" for time advancement and data exchange across simulators that meets the dependencies without loss of concurrency; (2) a hybrid scheduling strategy which adapts itself to the "right" level of pessimism/optimism based on the state of the execution and underlying dependencies. We also develop two key optimizations: (a) efficient checkpointing/rollback techniques; and (b) relaxation model for dependencies which guarantees bounded violation of consistency to support higher levels of concurrency. We evaluate our proposed techniques via a detailed case study from the emergency response domain by integrating three disparate simulators: a fire simulator (CFAST), an evacuation simulator (Drillsim) and a communication simulator (LTEsim).